MULTI-PIXEL PHOTON COUNTER FOR OPERATING A TABLETOP COSMIC RAY DETECTOR UNDER LOOSELY CONTROLLED CONDITIONS - Hoang Duy Thanh Nguyen; Vu Chi Lan Nguyen; Van Son Cao; Van Ngoc Tran; Khoa Nguyen; Thi Hong Van Nguyen; To Quyen Phan (Tạp chí Khoa học Đại học Đà Lạt)
The multi-pixel photon counter (MPPC) has recently emerged as a great type of silicon photomultiplier to replace or compensate for conventional vacuum-based photomultiplier tubes. An MPPC provides many advantageous features, such as high electrical gain, outstanding photon detection efficiency, fast timing response, immunity to magnetic fields, low-voltage operation, compactness, portability, and cost-effectiveness. This article examines the electrical and optical characteristics of an MPPC under loosely controlled environmental conditions. We also report a measurement of the light yield captured by the MPPC when a cosmic ray passes through the plastic scintillator, demonstrating that such a setup is suitable as a simple, cost-effective tabletop cosmic ray detector for educational and research purposes.